Ten thousand kilometres away and still the same species? The mystery of identity of Scopelocheirus sp. (Amphipoda: Scopelocheiridae) from the South Atlantic - Michael L. Zettler; Ralf Bastrop; James K. Lowry (Records of the Australian Museum, 2023)
During two campaigns, one in the Kattegat (Denmark) in 2018, and the other off Namibia in 2019, the same fish baited trap was applied to catch scavenging amphipods at two stations each. The water depths in both areas were between 50 and 130 m. In addition to very few individuals of other species (Isopoda and Amphipoda), the samples consisted mainly of Scopelocheirus sp. The species from the Kattegat was identified as S. hopei. The question arises as to whether it is possible that the same species could dominate scavenging communities in sea areas more than 10,000 km apart. At first glance, the scopelocheirid amphipods of the northern and southern hemispheres appear identical, but subtle morphological and large genetic differences led to the conclusion that we are dealing with a previously undescribed species off Namibia. We have named it Scopelocheirus sossi sp. nov.